Pengaruh Literasi Keuangan, Pengetahuan Keuangan, dan Sikap Keuangan Terhadap Kinerja Keuangan pada Pelaku UMKM Bisnis online di Bantul - Ayu Hanasri; Risal Rinofah; Pristin Prima Sari (Ekonomis: Journal of Economics and Business, 2023)
Economic growth cannot be separated from industrial development and advances in technology. Evidence of advances in technology is the existence of small businesses that run their businesses online. However, MSMEs/online entrepreneurs often experience fraud for investment reasons. One way to overcome these problems is to increase financial literacy, financial knowledge and financial attitudes so that people are financially literate and existing financial service products. Increasing financial literacy, financial knowledge and financial attitudes are the basic capital that is needed by online business MSMEs to minimize risks in management or decision making in order to improve financial performance. The purpose of this study was to examine the effect of financial literacy, financial knowledge, and financial attitudes on financial performance in online business MSMEs in Bantul. This study used a quantitative method using primary data obtained from questionnaires which were distributed online to online business MSMEs in Bantul, totaling 77 samples. The results of this study indicate that each financial literacy variable has an effect on financial performance, financial knowledge has an effect on financial performance, financial attitude has an effect on financial performance. Financial literacy, financial knowledge and financial attitudes influence financial performance.